Integrated Home-Based Palliative Care in Motor Neuron Disease: A Case Report from Low- Middle Income Country. Issue 4 (2nd October 2021) - Warrier, Manjusha G.; Sadasivan, Arun; Johnson, Jeremy; Vengalil, Seena; Nalini, Atchayaram; Thomas, Priya Treesa
Abstract: In many international care guidelines, multidisciplinary palliative care forms a key to optimum management in Motor Neuron Disease (MND). We describe the home-based palliative care interventions for a client with MND and his family from a Low and Middle-income country context. This report also discusses the advantages and challenges of the same with suggestions for sustaining the quality of care for neuro palliative conditions.